Pluvial periods in Southern Arabia over the last 1.1 million-years. (1st February 2020) - Nicholson, Samuel L.; Pike, Alistair W.G.; Hosfield, Rob; Roberts, Nick; Sahy, Diana; Woodhead, Jon; Cheng, Hai; Edwards, R. Lawrence; Affolter, Stéphane; Leuenberger, Markus; Burns, Stephen J.; Matter, Albert; et al.
Abstract: Past climates and environments experienced by the Saharo-Arabian desert belt are of prime importance for palaeoclimatic and palaeoanthropological research. On orbital timescales transformations of the desert into a grassland landscape in response to higher precipitation provided "windows of opportunity" for hominin dispersal from Africa into Eurasia. On long timescales, palaeoenvironmental reconstructions for the region are predominantly derived from marine sediments and available terrestrial records from the Arabian Peninsula are limited to 450 ka before present (BP). Here, we present a new stalagmite-based palaeoclimate record from Mukalla Cave in Yemen which extends back to ∼1.1 million years BP or Marine Isotope Stage (MIS) 31, as determined by Uranium-lead dating. Stalagmite Y99 grew only during peak interglacial periods and warm substages back to ∼1.1 Ma. Stalagmite calcite oxygen isotope (δ 18 O) values show that every past interglacial humid period was wetter than the Holocene, a period in which large lakes formed in the now arid areas of southern Arabia. Carbon isotope (δ 13 C) values indicate habitable grassland environments developed during these pluvial periods. A total of 21 pluvial periods with precipitation of more than 300 mm yr −1 occurred since ∼1.1 Ma and thus numerous opportunities for hominin dispersals occurred throughout the Pleistocene. New determinations of hydrogen (δ D FI ) and oxygen (δ 18 OFI ) isotopes in stalagmite fluid inclusion water demonstrates that enhanced precipitation in Southern Arabia was brought by the African and Indian Summer Monsoons. When combined with sub-annual calcite analysis of δ 18 O and δ 13 C, these data reveal a distinct wet (summer) and dry (winter) seasonality. Highlights: Pluvial periods recorded in stalagmites from Southern Arabia up to 1.073 Ma (MIS 31). Speleothem growth in Yemen only occurred during interglacial maxima and warm substages. The African Summer Monsoon (ASM) and Indian Summer Monsoon (ISM) increased precipitation to Southern Arabia. Grassland environments formed during pluvial periods. Grasslands provided "windows of opportunity" for hominin occupation of the Arabian interior and dispersals from Africa.